Targeted alpha anticancer therapies: update and future prospects - Allen BJ (Dove Medical Press, 2014)
Barry J Allen,1,2 Chen-Yu Huang,3 Raymond A Clarke2 1Faculty of Physics, University of Sydney, Sydney, NSW, Australia; 2Faculty of Medicine, Ingham Institute, University of Western Sydney, Liverpool, NSW, Australia; 3Central Clinical School, University of Sydney, Sydney, NSW, AustraliaAbstract: Targeted alpha therapy (TAT) is an emerging option for local and systemic cancer treatment. Preclinical research and clinical trials show that alpha-emitting radionuclides can kill targeted cancer cells while sparing normal cells, thus reducing toxicity. 223RaCl2 (Xofigo®) is the first alpha emitting radioisotope to gain registration in the US for palliative therapy of prostate cancer bone metastases by indirect physiological targeting. The alpha emitting radioisotopes 211At, 213Bi, 225Ac and 227Th are being used to label targeting vectors such as monoclonal antibodies for specific cancer therapy indications. In this review, safety and tolerance aspects are considered with respect to microdosimetry, specific energy, Monte Carlo model calculations, biodosimetry, equivalent dose and mutagenesis. The clinical efficacy of TAT for solid tumors may also be enhanced by its capacity for tumor anti-vascular (TAVAT) effects. This review emphasizes key aspects of TAT research with respect to the PAI2-uPAR complex and the monoclonal antibodies bevacizumab, C595 and J591. Clinical trial outcomes are reviewed for neuroendocrine tumors, leukemia, glioma, melanoma, non-Hodgkins lymphoma, and prostate bone metastases. Recommendations and future directions are proposed.Keywords: biodosimetry, microdosimetry, mutagenesis, PAI2, bevacizumab, C595, J591, tumors, cancer, metastases